2007
DOI: 10.1038/sj.bmt.1705806
|View full text |Cite
|
Sign up to set email alerts
|

Time to first flare-up episode of GVHD can stratify patients according to their prognosis during clinical course of progressive- or quiescent-type chronic GVHD

Abstract: GVHD-specific survival (GSS) has been investigated as a potential study end point to describe the clinical course and outcome of chronic GVHD (cGVHD). However, reaching this end point requires a long observation time. We hypothesized that the time to the first flare-up (FFU) of cGVHD (TTF) can be an alternative statistical end point to GSS. This retrospective study included 96 patients with a diagnosis of cGVHD from a cohort of 119 patients with a prior history of acute GVHD. The median TTF was 73 days after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Our results confirmed those reported by Kim et al 11 in demonstrating that exacerbation of chronic GVHD is associated with an increased risk of non-relapse mortality and with decreased overall survival. As in the Korean study, the associations with non-relapse mortality and survival endpoints are stronger for early exacerbation than for late exacerbation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirmed those reported by Kim et al 11 in demonstrating that exacerbation of chronic GVHD is associated with an increased risk of non-relapse mortality and with decreased overall survival. As in the Korean study, the associations with non-relapse mortality and survival endpoints are stronger for early exacerbation than for late exacerbation.…”
Section: Discussionsupporting
confidence: 92%
“…Kim et al 11 recently proposed that an early flare or exacerbation of chronic GVHD could be used as an endpoint in clinical trials. Early flare was strongly associated with decreased GVHD-specific survival, i.e., increased non-relapse mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that nearly all patients who developed overlap syndrome had a prior history of aGVHD in our study cohort, NIH overlap syndrome in most instances could be considered as a flare of preexisting aGVHD, concomitant with development of classic cGVHD. In this context, it is important to note that early flare of cGVHD or early treatment change for exacerbation of cGVHD has been reported to be associated with increased NRM and inferior cGSS [34,35]. It is also of note that a significantly higher proportion of patients with overlap syndrome had thrombocytopenia less than 100 9 10 3 /lL at cGVHD onset in our study.…”
Section: Discussionmentioning
confidence: 84%
“…9,10 We also demonstrated that addition of a new treatment was associated with higher non-relapse and overall mortality, which is in agreement with previous studies. 15,16 Inamoto et al published two analyses of FFS in patients who received first-line 9 or second-line 10 therapy for chronic GVHD at a single institution. The median duration of FFS and the rates of FFS at 6 months and 2 years in the current study are similar to their results 9,10 despite the differences in cohort definition.…”
Section: Discussionmentioning
confidence: 99%